Вибір спеціалізованих інтернет-порталів як засобів маркетингових комунікацій підприємства - Савченко, Ю. Т.; Шуліченко, А. Є.; Карий, О. І. (Видавництво Львівської політехніки, 2012)
Проаналізовані характеристики Інтернет-порталів як засоби маркетингових комунікацій підприємства та досліджено специфіку спеціалізованих Інтернет-порталів з продажу будівельних матеріалів та послуг. На основі проведеного аналізу визначено ключові характеристики Інтернет-порталів, на які слід звертати увагу підприємствам під час вибору місця розташування інформації про себе та свої товари. The characteristics of Internet-portals as tools of marketing communications of an enterprise are analyzed as well as the specifics of specialized Internet portals for constructional material and services are investigated in the article. It is proved that choosing an Internet-portal for promotion an enterprise have to evaluate number of its visitors and the geography of these visitors; whether these visitors find the portal via searching servers or directly (they are patrons); how much time visitors spend on the portal and whether they go further to enterprise sites from this portal. The popularity of searching servers for finding out new information among Internet users rises up the importance of such characteristics of a portal as PageRank and the number of indexed objects on the portal. Of course, the important role also plays the price for presenting information about an enterprise on the portal and the convenience of presented information about an enterprise editing.
Сhoosing specialized internet-portals as tools of marketing communications of an enterprise
Keywords: підприємство; маркетингові комунікації; Інтернет-портал; реклама; Інтернет; електронна комерція; enterprise; Internet-portal; advertising; Internet; e-commerce; marketing communications